Reducing the Bitter Taste of Virgin Olive Oil Don Carlo by Microbial and Vegetable Enzymes Linked to the Colloidal Fraction - Biagi Angelo Zullo (Colloids and Interfaces, 2020)
Bitter taste is a positive sensory attribute that correlates with the concentration of phenols in olive oil. However, excessive bitterness can be perceived by consumers as a negative attribute. The aim of this investigation was to improve the process of debittering Don Carlo extra virgin olive oil (EVOO), which is rich in phenols, through blending with newly produced Leccino EVOOs, which can provide high oleuropeinolytic activity. The debittering process of blending Don Carlo EVOO with two types of Leccino EVOOs (decanter and settled EVOO), was carried out during three months of storage in canisters placed in fixed positions, or periodically inverted to prevent sedimentation. The reduction in phenolic concentration and bitterness index (K225 value) reached maximum values of 51% and 42% respectively in Don Carlo EVOO mixed with Leccino settled EVOO after three months of storage in periodically inverted containers. Analytical indices and sensory analysis, in accord with bitterness index (K225) results, confirmed a reduction or elimination of bitter taste in the oil samples depending on the type of Leccino EVOO added, and the sample storage method. All analytical results remained within parameters established by the European Community regulations for commercial merceological class EVOO.